Introduction of cadmium chloride additive to improve the performance and stability of perovskite solar cells. Issue 32 (15th July 2022) - Mohammed, Mustafa K. A.; Jabir, Majid S.; Abdulzahraa, Haider G.; Mohammed, Safa H.; Al-Azzawi, Waleed Khaild; Ahmed, Duha S.; Singh, Sangeeta; Kumar, Anjan; Asaithambi, S.; Shekargoftar, Masoud
Abstract : With the increase in the importance of using green energy sources to meet the world's energy demands, attempts have been made to push perovskite solar cell technology toward industrialization all around the world. Abstract : With the increase in the importance of using green energy sources to meet the world's energy demands, attempts have been made to push perovskite solar cell technology toward industrialization all around the world. Improving the properties of perovskite materials as the heart of PSCs is one of the methods to fabricate favorable photovoltaic (PV) solar cells based on perovskites. Here, cadmium chloride (CdCl2 ) was used as an additive source for the perovskite precursor to improve its PV properties. Results indicated CdCl2 improves the perovskite growth and tailors its crystalline properties, suggesting boosted charge transport processes in the bulk and interfaces of the perovskite layer with electron–hole transport layers. Overall, by incorporation of 1.0% into the MAPbI3 layer, a maximum power conversion efficiency of 15.28% was recorded for perovskite-based solar cells, higher than the 12.17% for the control devices. The developed method not only improved the PV performance of devices but also boosted the stability behavior of solar cells due to the passivated domain boundaries and enhanced hydrophobicity in the CdCl2 -based devices.